Peningkatan Kemampuan Bercerita Anak Usia 5-6 Tahun di TK Menggunakan Media Boneka Tangan - Fitasari, Nurul; Wulandari, Rifa Suci; Mustikasari, Rizki (STKIP PGRI Ponorogo Press, 2025)
Language is one of important aspect of development to be stimulated. The storytelling method using hand puppets can be used to stimulate children's language skills. The aim of this research is to determine the improvement of storytelling abilities on children aged 5-6 years at Kindergarten using hand puppets. This research used classroom action research design (CAR) which was divided into two cycles and started with a pre-cycle. Each cycle consisted of planning, action, observation and reflection. The research subjects were children aged 5-6 years or group B at Kindergarten. Data collection used observation and documentation instruments. The quantitative data analysis technique used a paired sample t-test in a single group. The normality test was carried out before testing the research hypothesis. The results of the research showed an increase, namely the average pre-cycle student score was 10.08, the first cycle average was 11.50 and the second cycle average score increased by 14.25. From the output results of SPSS 25 data analysis, it showed a significance value (2-tailed) for the Paired Difference column of 0.000<0.05. Meanwhile, the results of the t calculated paired sample t test showed that the value between pre-cycle and cycle 1 showed that the calculated t value was greater than the t table 7.340 > 1.7459. In cycles I and Cycle II, the calculated t value was greater than the t table, 12.638 > 1.7459. Based on the decision-making criteria, it can be concluded that H0 was rejected and Ha was accepted, which means that children's storytelling abilities are significantly different by the using of hand puppet media.